Editor's Foreword - Vadim Radaev (Journal of Economic Sociology, 2022)
Dear colleagues, Events that started on February 24, 2022 brought radical changes to Russia and the whole world. Both academic activity and daily life have become much more uncertain and complicated. Quite quickly, many members of the  nternational Board cancelled their affiliations with our Journal. We really appreciate the attitude of those who did not cancel their cooperation with us on the basis of our nationality. Despite all expected difficulties, we have to fulfil our professional duties and present to you the next issue of our journal.